Manajemen Pembelajaran Berbasis Trikon (Kontinyu, Konvergen, dan Konsentris) di SD Negeri Jurangombo 4 Kota Magelang - Afianie Halim Sawarso (Media Manajemen Pendidikan, 2022)
This study aims to describe (1) the learning management based on trikon (continue, convergent, and concentrate) at SD Negeri Jurangombo 4 Magelang City, (2) Creativity and Innovation in learning management based on trikon (continue, convergent, and concentrate), (3) the supporting and inhibiting factors faced when participating in managing learning based on trikon (continue, convergent, dan concentrate) at SD Negeri Jurangombo 4. This study uses a qualitative approach with a descriptive type. Sources of research data are the school principal dan teachers of SD Negeri Jurangombo 4. Data collection techniques using in-depth interview techniques and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. Test the validity of the data using technical triangulation. The results of the study indicate that (1) the learning management based on trikon (continue, convergent, dan concentrate) at SD Negeri Jurangombo 4 running smoothly, (2) Teachers of SD Negeri Jurangombo 4 make learning innovation with the support of the school principal, and (3) the supporting and inhibiting factors faced when participating in managing learning based in trikon (continue, convergent, dan concentrate) is from the teachers, educational institution, and the school itself, and the solution for the problems is to have discussion with colleagues.